Pendampingan Penulisan Karya Ilmiah Penelitian Tindakan Kelas Bagi Guru-Guru Di Kota Bajawa Kabupaten Ngada - Moses Kopong Tokan; Mbing Maria Imakulata; I Wayan Sukarjita; Marsi D.S. Bani (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
In general, teachers in Bajawa City, Ngada Regency do not understand Classroom Action Research. Related to this, the purpose of this activity is to provide teachers with an understanding of CAR, proposal writing, report writing, article writing and how to publish it. This activity is carried out with the stages of coordination, online socialization and assistance in writing articles. The results of the activity showed that the participants already had an understanding of classroom action research and were able to write drafts of articles.